HCI in games : first international conference, HCI-Games 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019 : proceedings /: first international conference, HCI-Games 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019 : proceedings. ([2019]) - Unknown
No abstract available